1992
DOI: 10.1063/1.352145
|View full text |Cite
|
Sign up to set email alerts
|

Deposition mechanism of hydrogenated hard-carbon films in a CH4 rf discharge plasma

Abstract: To examine the mechanism of film deposition in a planar rf CH4 discharge plasma, measurements were made of the spatial distributions of the deposition rate and optical emission intensity along the discharge axis between parallel electrodes. Optical-absorption properties of the deposited carbon films were also measured over both the infrared and visible regions. To measure the spatial deposition rates, the substrate surface was elevated from the cathode electrode with the use of quartz glass plates. It was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(72 citation statements)
references
References 61 publications
3
67
0
2
Order By: Relevance
“…They quantified the boundary between the ion energy flux limited regime and the F-atom flux limited regime. Mutsukura et al 11 studied the deposition of hydrogenated hard-carbon films in a CH 4 rf discharge plasma. They found at high pressure that the film deposition rate was predominantly dependent on the ion energy flux.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They quantified the boundary between the ion energy flux limited regime and the F-atom flux limited regime. Mutsukura et al 11 studied the deposition of hydrogenated hard-carbon films in a CH 4 rf discharge plasma. They found at high pressure that the film deposition rate was predominantly dependent on the ion energy flux.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14] showed that plasma etching and deposition rates of plasma perfluoropolymer thin films have a similar dependence on ion energy. Ding et al 10 found in an electron cyclotron resonance ͑ECR͒ etcher that the etch rates of SiO 2 with CF 4 /O 2 /Ar plasmas only depend on ion energy flux and F-atom density.…”
mentioning
confidence: 99%
“…To obtain higher deposition rate, the non-trench Si substrate on which films deposited was set on a stainless steel step of 20 mm in height [22,23]. The substrate temperature was 100 °C.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…2c). When the CH 3 radicals abundantly exist in plasma, CH3 radicals are adsorbed on the growing surface and promote film growth [15]. The CH3 radicals decrease with increased microwave power, then these result lead to a decrease of deposition rate.…”
Section: Deposition Ratementioning
confidence: 99%